Unraveling the role of gut microbiota and immune cells in thyroid cancer and tumor drug resistance - Jiaqin Deng; Yihua Gu; Ming Yu; Yeqian Lai; Lihong Qiu (Discover Oncology, 2024)
Abstract The gut microbiota (GM) and immune cells (IC) are increasingly recognized as key players in cancer development and progression. This study aimed to explore the potential mediating role of IC in the causal relationship between GM and thyroid cancer (TC) using Mendelian randomization (MR) analysis. Data from genome-wide association studies (GWAS) encompassing 473 GM species, 731 IC types, and TC were utilized. MR analysis identified nine GM species with significant causal relationships to TC, mediated by 10 IC phenotypes such as "Switched Memory AC," "IgD-CD38dim AC," and "EM DN (CD4-CD8-) AC." These findings suggest a complex interplay where specific IC mediate the effects of GM on TC risk. Sensitivity analyses confirmed the robustness of these results, with no evidence of horizontal pleiotropy. This study highlights potential mechanisms linking GM and IC to TC, offering insights that could inform GM-based immunotherapeutic strategies and IC-targeted interventions. However, further experimental research is needed to validate these causal pathways and better understand the underlying biological mechanisms.